Hybrid Water Feedback Solutions Using Internet of Thing (IoT) Enabled Water Pumps Powered by Solar Panels - Achmad Buchori; Adhi Kusmantoro; Aan Burhanuddin; Takashi Hiyama (Scientific Journal of Informatics, 2023)
Purpose: Renewable energy in Indonesia is very abundant, one of which is solar energy. With Indonesia's location on the equator, the abundant potential of solar energy can be utilized as an environmentally friendly source of electricity. To increase the potential of solar energy as a source of electricity, it is equipped with a battery storage system. The most widely used electrical energy storage system is the battery. The purpose of this study is the use of solar energy for DC water pumps. The proposed system is also equipped with power, voltage and current monitoring on the solar panel side and on the load side (water pump).Methods/Study design/approach: The method used is to conduct a literature review to study and find out the development of a power monitoring system using solar panels. The next step is to measure solar radiation, calculate PV capacity and SCC. Furthermore, designing, modeling, simulating, analyzing, and implementing the optimal topology for water pump control using solar panels.Result/Findings: The results of the research are water pump control coordination devices using Sonoff with an IoT-based monitoring system. This device is capable of controlling PV and battery power flow. A prototype of a solar water pump has been produced which has been validated by experts in the field of appropriate technology with feasible results and received a positive response from farmers in Demak to be immediately implemented in the fields to help with the water crisis in agricultural landNovelty/Originality/Value: the advantage of this solar water pump is that the product is equipped with the internet of things (IoT) which can control the use of water pumps in the fields with our android devices wherever we are, this makes it easy for farmers to apply them, then the water pumps also do not use electricity which makes this water pump not harmful to farmers, because in the past many farmers were electrocuted and died.